2015
DOI: 10.1007/s00168-015-0680-2
|View full text |Cite
|
Sign up to set email alerts
|

Variety, economic growth and knowledge intensity of European regions: a spatial panel analysis

Abstract: Although the theoretical framework on agglomeration externalities and the channels through which they influence the regional economy appear well established, the empirical evidence on their magnitude and impact has been rather ambiguous and inconclusive. Applying the concepts of related and unrelated variety to an interregional European dataset and using spatial panel analysis, this paper provides critical information on the type and functioning of agglomeration externalities in relation to regional heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 51 publications
8
43
0
4
Order By: Relevance
“…More recently, Cortinovis and Van Oort (2015) conducted their research using a panEuropean data set. Following the original set-up of the study by Frenken et al (2007), they hypothesize that related variety is positively related to employment growth due to knowledge spillovers across sectors; unrelated variety is negatively related to unemployment growth due to portfolio effects associated with a diversified economy and as a result dampened effects of sector-specific shocks.…”
Section: Related-variety Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Cortinovis and Van Oort (2015) conducted their research using a panEuropean data set. Following the original set-up of the study by Frenken et al (2007), they hypothesize that related variety is positively related to employment growth due to knowledge spillovers across sectors; unrelated variety is negatively related to unemployment growth due to portfolio effects associated with a diversified economy and as a result dampened effects of sector-specific shocks.…”
Section: Related-variety Studiesmentioning
confidence: 99%
“…Those who looked at inter-industry differences found that the effects of related variety on growth may be specific to certain industries only, especially manufacturing and knowledge-intensive ones (Bishop & Gripaios, 2010;Bosma et al, 2011;Cortinovis & Van Oort, 2015;Hartog et al, 2012). Concerning the studies looking on how countries or regions develop new industries following Hidalgo et al (2007), it was also found that if a region or countries already host industries that are related to a specific industry, it is much more likely to become specialized in that industry.…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we investigate in a spatial panel setting with region and year fixed effects whether and how network relations affect local productivity, once the spatial proximity dimension is controlled for. Secondly, we specifically model network relations with most knowledge and technologically advanced regions (Wintijes and Hollanders 2010, Cortinovis and Van Oort 2015) to study whether such linkages provide directed spillover effects. Thirdly, we test whether the stock of absorptive capabilities of regions (on an educational level) act as precondition for regions to profit (take in) from network relations with most advanced regions (Miguelez and Moreno 2015, Cortinovis andVan Oort 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we specifically model network relations with most knowledge and technologically advanced regions (Wintijes and Hollanders 2010, Cortinovis and Van Oort 2015) to study whether such linkages provide directed spillover effects. Thirdly, we test whether the stock of absorptive capabilities of regions (on an educational level) act as precondition for regions to profit (take in) from network relations with most advanced regions (Miguelez and Moreno 2015, Cortinovis andVan Oort 2015). Finally, we check the validity of our potentially endogenous results with an instrumental variable (IV) strategy, in which illiteracy rates and gross reproduction rates in European regions in the early 1930s are used as an instrument for current R&D expenditures.…”
Section: Introductionmentioning
confidence: 99%